(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Wireless network has become the most popular technology among current communities due to cheap hardware, mobility, ease of installation, usage and expandability. Remote system has turned into the most well known innovation among current groups because of modest equipment, portability, simplicity of establishment, use and expandability. There- fore, the performance of WLANs becomes important. Jamming attackers would reduce the performance of wireless network such as decreasing throughput, increasing delay and data dropped ... etc. The IEEE 802.11 standard specifies two different media access con- trol (MAC) mechanisms: distributed coordination function (DCF), point coordination function (PCF). The IEEE 802.11 standard determines two distinct media get to control (MAC) components: disseminated coordination works (DCF), point coordination work (PCF). PCF achieve higher throughput than DCF, therefore, this study investigates the integration of PCF in WLAN which is attacked by Jammers. This study is done using OPNET Modeler (v14.5). OPNET Modeler (v14.5) is used in this work, because it is the more suitable tool for wireless network. After the simulation was run, the results were collected and showed that PCF gave a good improvement by increasing throughput and decreasing data dropped with an acceptable delay even when the transmission power of Jammer was increased more above the transmission power of computers and PCF also gave a good improvement in throughput and delay when the number of Jammers became two. This would improve the performance of the system.